2018
DOI: 10.3390/ani8110207
|View full text |Cite
|
Sign up to set email alerts
|

Animal Welfare and Mountain Products from Traditional Dairy Farms: How Do Consumers Perceive Complexity?

Abstract: Simple SummaryEuropean consumers recognize the added value of mountain dairy production and relate it to a composite of positive attributes. However, while consumers’ understanding of conventional dairy production and animal welfare has already been investigated, how consumers perceive animal welfare in traditional mountain dairy farming remains unexplored. This qualitative study aims at shedding light on consumers’ perceptions regarding animal welfare in mountain dairy cheese production systems. Focus group i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 22 publications
4
39
1
3
Order By: Relevance
“…Lower production and traditional management practices could thus mitigate the production disease risk and the need for AM. The findings on the relationship between herd size, milk yield, and AMU also correspond to consumers' perceptions of antimicrobial use in different farming systems [24].…”
Section: Discussionsupporting
confidence: 63%
“…Lower production and traditional management practices could thus mitigate the production disease risk and the need for AM. The findings on the relationship between herd size, milk yield, and AMU also correspond to consumers' perceptions of antimicrobial use in different farming systems [24].…”
Section: Discussionsupporting
confidence: 63%
“…In fact, tourists did not seem to associate summer farms with grazing livestock systems, as showed by the low frequency of the words "livestock" and "Alpine pastures". Moreover, Zuliani et al [48] demonstrated a gap between the consumers' conception of mountain farming systems and the actual farming practices. The only semantic group that was highly frequent in both categories was "products".…”
Section: Discussionmentioning
confidence: 99%
“…Ethical and social issues in sustainable food labels mainly regard animal well-being [30,[33][34][35][36] and fair-trade certification [37,38]. Nowadays, livestock production techniques are mainly based on intensive practices, and in recent years the rising consumers' awareness about food production process has led to a growing interest in food produced respecting animal well-being [33].…”
Section: Sustainable Certification Systems and Choice Experimentsmentioning
confidence: 99%
“…As explained before, green consumption attitudes can be based on moral norms and beliefs that can influence the purchasing actions; among these convictions is a place for the respect for animal welfare [61]. In fact, the animal welfare concept includes societal and personal values and ethical beliefs [35] and can lead purchasing choices. Moreover, intensive livestock systems have impacted consumer sensitivity, contributing to change consumption habits [35].…”
Section: Consumers' Pro-environment Behavior In Food Choices With Attmentioning
confidence: 99%